EXPERIMENTAL STUDY TO SCREEN AND OPTIMIZE VARIOUS FOAM FLOODING TECHNIQUES USING SPECIALLY DESIGNED AUTOMATED SYSTEM - NASR, NEGAR HADIAN (2018)
Gas-assisted EOR is a proven technology, it often encounters frontal instabilities such as gravity segregation, fingering, and channeling of gas phase through high permeability layers/streaks; all of which cause inadequate sweep efficiency